Characteristics of superior soybean breeding lines tolerance to rust (Phakopsora pachyrhizi Syd.) - Alfi Inayati; Eriyanto Yusnawan (Biosaintifika: Journal of Biology & Biology Education, 2016)
Soybean rust caused by Phakopsora pachyrhizi is one of the most important diseases which limits soybean production. The aim of this study was to evaluate the resistance of 28 superior soybean lines and their tolerance to rust. The study was conducted at a screen house and arranged in a completely randomized design (CRD); three replications. All genotypes tested were artificially inoculated with P. pachyrhizi, and a set of un-inoculated genotypes was planted as a comparison. Number of pustules was recorded weekly, and resistant criteria was rated based on the International working group on soybean rust IWGSR method. Lesion color (LC), sporulation level (SL), number of uredia (NoU), frequency of pustule which had uredia, and yield were also recorded. Among 28 genotypes tested, only one was categorized as resistant and 2 genotypes were susceptible. Resistant genotypes had few pustules, lower AUDPC values, low disease severity, and Reddish Brown lesion type. Soybean rust affected yield components, i.e. number of intact pods and yield per plant. Yield loses due to rust in this study varied from 5-89%, and the average was 51%. The set of lines from Tanggamus pedigree showed more resistant to rust but less tolerant compared to Sinabung pedigree.How to CiteInayati, A., Yusnawan, E. (2016). Characteristics of superior soybean breeding lines tolerancet to rust (Phakopsora pachyrhizi Syd.). Biosaintifika: Journal of Biology Biology Education, 8(1), 47-55.